Concurrent sexual and substance-use risk behaviours among female sex workers in Kenya's Coast Province: Findings from a behavioural monitoring survey - Simon-Pierre Tegang; S. Abdallah; G. Emukule; S. Luchters; N. Kingola; M. Barasa; S. Mucheke; P. Mwarogo (Taylor & Francis Group, 2010)
While many studies confirm the association between HIV, alcohol and injecting drug use by female sex workers (FSWs), little is known about their use of marijuana, khat and other substances and the association of these substances with HIV, risky sexual behaviour, and sexual violence. To better understand this association, data were analysed from a cross-sectional, behavioural survey of 297 FSWs in Mombasa, a well-known tourist destination and the second largest port in Africa and capital city of the Coast Province in Kenya.Among the FSWs, lifetime use of different substances was reported by 91% for alcohol, 71% for khat, 34% for marijuana, and 6% for heroin, cocaine, glue or petrol. The majority (79%) used more than one substance, and multiple-substance use was reported by all respondents who ever used marijuana, heroin, cocaine, glue and petrol. The risk of HIV acquisition was perceived as medium to high by 41% of respondents, 75% of whom attributed this risk to multiple partners. Sexual violence was reported by 48% of respondents, and 30% indicated that this happened several times. Despite HIV prevention programmes targeting FSWs in Mombasa, most of them continue to engage in risky sexual behaviours. This suggests that harm reduction strategies for substance use should be coupled with efforts to promote consistent condom use and partner reduction.